Network Slicing for 5G and Beyond Networks - Kazmi, S. M. Ahsan; Khan, Latif U.; Tran, Nguyen H.; Hong, Choong Seon.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides a comprehensive guide to the emerging field of network slicing and its importance to bringing novel 5G applications into fruition. The authors discuss the current trends, novel enabling technologies, and current challenges imposed on the cellular networks. Resource management aspects of network slicing are also discussed by summarizing and comparing traditional game theoretic and optimization based solutions. Finally, the book presents some use cases of network slicing and applications for vertical industries. Topics include 5G deliverables, Radio Access Network (RAN) resources, and Core Network (CN) resources. Discusses the 5G network requirements and the challenges therein and how network slicing offers a solution Features the enabling technologies of future networks and how network slicing will play a role Presents the role of machine learning and data analytics for future cellular networks along with summarizing the machine learning approaches for 5G and beyond networks.
Introduction -- 5G Networks -- 5G Deliverable -- 5G Networks: Industrial efforts -- Challenges to realize 5G Networks -- Network Slicing -- Network Slicing Enablers -- Wireless Network Virtualization -- Evolution of Cellular Networks -- Network Slicing: Industrial Efforts and Use Cases -- Machine Learning and Network Slicing -- Role of Machine Learning and Data Analytics in Network Slicing -- Machine Learning Deliverable for 5G Networks -- Resource Management for Network Slicing -- Radio Access Network (RAN) resources -- Core Network (CN) Resources -- Resource management approaches for Network Slicing -- Network Slicing: Use-Cases for Vertical Industries -- Conclusion.
Keywords: Telecommunication; Computer networks .; Computational intelligence; Pattern recognition systems; Communications Engineering, Networks; Computer Communication Networks; Computational Intelligence; Automated Pattern Recognition